Vegetation structure, species diversity, and mangrove zonation patterns in the Tanjung Panjang Nature Reserve Area, Gorontalo, Indonesia - Dewi Wahyuni Baderan; Ramli Utina; Nuraini Lapolo (International Journal of Applied Biology, 2018)
This study aimed to analyze the structure of vegetation, diversity and patterns of mangrove zonation in the Tanjung Panjang Nature Reserve area. Data collection of mangrove vegetation structure was carried out by using the line transect method (plot measuring 20 m x 20 m), measurement of environmental parameters that supported mangrove life, and 12 soil samples carried out by laboratory tests. The sample distribution was 18 research sample points. The results showed that mangrove vegetation density both at the level of trees, saplings and seedlings was in the category of total damage with density values at tree level 0.04-0.22 ind/ha), sapling 0- 0.07ind/ha), and seedlings 0.02-0.08 ind/Ha). The percentage of closure types ranged from 0% - 38%, meaning that the criteria of damage was rare, which was <50%, and some were included in the criteria of total damage, which was 0%. The index of mangrove species diversity was sequential starting from the level of trees, saplings and seedlings, which were 0.37-1.53, 0.00-0.31, and 0.00, where the tree level diversity index was in the medium category, and the sapling and seedling levels were in the low category.